Retinal microcirculation abnormalities in patients with systemic sclerosis: an explorative optical coherence tomography angiography study - Carnevali, Adriano; Giannaccare, Giuseppe; Gatti, Valentina; Battaglia, Caterina; Randazzo, Giorgio; Yu, Angeli Christy; Pellegrini, Marco; Ferragina, Francesco; Toro, Mario Damiano; Bruno, Caterina; Scorcia, Vincenzo; Ursini, Francesco (Rheumatology (Oxford, England), 2021)
Abstract Objectives To investigate subclinical and clinical abnormalities in retinal and choroidal vascular plexuses in patients with SSc by means of optical coherence tomography angiography (OCT-A). Methods A total of 20 consecutive SSc patients were recruited and compared with 20 healthy subjects. Quantitative analysis of vessel density (VD), choriocapillaris plexus flow index (CCP-FI) and choroidal vascularity index were performed on OCT-A images in the superficial capillary plexus (SCP), deep capillary plexus (DCP) and CCP for all patients. Images were further reviewed by two independent readers for the assessment of qualitative abnormalities, including tortuosity, rarefaction areas, megacapillaries and macular-foveal capillaries. Results The DCP-VD in the whole scan and in the perifoveal, superior, inferior, nasal and temporal regions was significantly lower in the SSc group. The CCP-FI was significantly higher in SSc patients. When comparing SSc patients with and without digital ulcers, significantly decreased SCP-VD was demonstrated in the whole, perifoveal, superior, inferior, temporal and nasal regions. No difference in any of the OCT-A parameters was observed when comparing patients with and without interstitial lung disease. Qualitative analysis of OCT-A revealed at least one abnormality in 95% of patients. Conclusion We showed the ability of OCT-A to disclose early ocular vascular abnormalities in patients with SSc. Our results may represent a hypothesis-generating basis for exploring the potential role of OCT-A in diagnosis, monitoring and prognosis stratification in SSc.